ICT in higher education. The review process of an assessment tool of technological competences of students with visual impairments - Rosa Bellacicco; Alessia Farinella (Firenze University Press, 2018)
The use of technological tools in academic settings may play a crucial role in promoting students' success, especially with regard to students with special educational needs. This paper presents and discusses the results of the review process of the items of an assessment tool of technological competences of students with visual impairment. The tool has been developed within the context of a wider research project of the University of Turin. The paper concludes with a reflection on the improvement of academic teaching aimed at promoting more inclusive educational contexts. ICT in università. Processo di revisione di un protocollo di valutazione delle competenze tecnologiche degli studenti con disabilità visiva In ambito universitario l'uso delle risorse tecnologiche contribuisce a promuovere il successo formativo, soprattutto per gli studenti con disabilità. Il contributo presenta e discute i risultati di un processo di revisione degli item di un protocollo di valutazione delle competenze tecnologiche degli studenti con disabilità visiva strutturato nell'ambito di una più ampia ricerca dell'Università di Torino. L'articolo si conclude con una riflessione sul potenziamento della didattica accademica ai fini della costruzione di assetti formativi più inclusivi.